2020
DOI: 10.4236/ojog.2020.1090123
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid and Ethamsylate for Reducing Blood Loss in Patient Undergoing Lower Segment Cesarean Section at High Risk for Post-Partum Hemorrhage: A Pilot Study

Abstract: Objective: To assess the efficacy of intravenous tranexamic acid and ethamsylate in reducing blood loss during and after elective lower segment cesarean delivery in patients at high risk for postpartum hemorrhage. Methods: A double-blind, randomized placebo-controlled study was undertaken of women undergoing elective lower-segment cesarean delivery of a full-term pregnancy at high risk for postpartum hemorrhage at Ain Sham University Maternity Hospital in Cairo, Egypt, between January 2019 and October 2019. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…The current study revealed that there is No significant difference between the studied groups regarding age, BMI, parity, gestational age, and indications of cesarean section. Which was supported by study of (Alanwar & Gamal, 2020) 14 as they reported that there was no significant difference as regard patient characteristics (age, weight, BMI, and gestational age) between study and control groups.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The current study revealed that there is No significant difference between the studied groups regarding age, BMI, parity, gestational age, and indications of cesarean section. Which was supported by study of (Alanwar & Gamal, 2020) 14 as they reported that there was no significant difference as regard patient characteristics (age, weight, BMI, and gestational age) between study and control groups.…”
Section: Discussionmentioning
confidence: 63%
“…According to (Alanwar & Gamal, 2020) 14 they demonstrated that intraoperative intravenous administration of tranexamic acid together with ethamsylate given just after delivery of the fetus is an effective method for reduction of blood loss during elective lower-segment cesarean delivery. Furthermore, tranexamic acid and ethamsylate reduce the need for ecbolic drugs during the postoperative period and reduces the postpartum blood loss in patients with high risk for postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Uterotonic drugs are used as prophylactic measures to decrease the bleeding amount whether intra-operative or post-operative such as ergometrine, prostaglandin E1, prostaglandin F2α, carbetocin, and oxytocin [ 11 ]. Other drugs can be used to activate the hemostasis process such as tranexamic acid and ethamsylate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been clinically established that intravenous TXA reduces surgical blood loss and mortality due to bleeding without any obvious safety issues in surgical patients and as well reduces the need for blood transfusion 16,17 . However, much work has not been done in evaluating the haemostatic effect of intravenous ETH in major gynaecological surgeries 18 .…”
Section: Discussionmentioning
confidence: 99%
“…They noted that TXA and ETH improved health-related quality of life in women with menorrhagia by reducing blood loss, with TXA demonstrating superior haemostatic effect over ETH. There is dearth of literature on haemostatic effect of ETH on gynaecological surgeries; Alanwar et al 18 reported in 2020, that no previous clinical trial has investigated the role of ETH in either prophylaxis or treatment of hemorrhage during surgery, that their study was the first to do so. However, they evaluated the combination of TXA and ETH in Cesarean delivery, and noted that the study drugs significantly reduced intraoperative and postoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%